Years of dermatology experience and geographic region are associated with outlier performance of excision or destruction for nonmelanoma skin cancer - Brad R. Woodie; Scott A. Neltner; Annabella G. Pauley; Alan B. Fleischer (Taylor & Francis Group, 2023)
Introduction Treatments for nonmelanoma skin cancer (NMSC) include excision (surgical removal) and destruction (cryotherapy or curettage with or without electrodesiccation) in addition to other methods. Although cure rates are similar between excision and destruction for low-risk NMSCs, excision is substantially more expensive. Performing destruction when appropriate can reduce costs while providing comparable cure rate and cosmesis. Objective To identify characteristics associated with exclusive (outlier) performance of excision or destruction for NMSC. Methods The study consisted of malignant excision and destruction procedures submitted by dermatologists to Medicare in 2019. Proportions of services for each method were analyzed with respect to geographic region, years of dermatology experience, median income of the practice zip code, and rural-urban commuting area (RUCA) code. Results Fewer years of experience predicted a higher proportion of excisions (R2 = 0.7, p < .001) and higher odds of outlier excision performance. Outlier performance of excision was associated with practicing in the South, Midwest, and West, whereas outlier performance of destruction was associated with practicing in the Northeast and Midwest. Conclusions Dermatologists with less experience or in certain geographic regions performed more malignant excision relative to destruction. As the older population of dermatologists retires, the cost of care for NMSC may increase.